Terapi Fotodinamik Mempercepat Kesembuhan Luka Insisi pada Kulit Tikus Putih (Rattus novergicus) yang Diinfeksi Bakteri Methicilin-Resistant Staphylococcus aureus - Budianto, Yonatan Dimascahyo; Suwanti, Lucia Tri; Yuniarti, Wiwik Misaco; Plumeriastuti, Hani; Tyasningsih, Wiwiek; Setiawan, Boedi (Jurnal Veteriner, 2020)
The aims of this research was to determine the effect of photodynamic therapy (PDT) on the healing of incision wounds in rat skin (Rattus norvegicus) that infected with MRSA bacteria by evaluating and give a score (0 – 4) at wound healing factors such as epithelialization, angiogenesis, inflammatory cells, fibroblast cells and collagen density. This study used 25 white rats divided randomly into 5 groups with 5 replications, namely P0 = MRSA infection wound + Povidone Iodine, P1 = MRSA infection wound + Silver Sulfadiazine, P2 = MRSA infection wound + 5-minute PDT irradiation, P3 = MRSA infection wound + 10- minute PDT irradiation and P4 = MRSA infection wound + 15-minute PDT irradiation. Histopathological observations and scoring showed epithelialization and collagen density in groups P2, P3 and P4 increased significantly compared to groups P0 and P1 (p<0.05). The histopathological observations and scoring of angiogenesis, inflammatory cells, fibroblast cells of P0 and P1 groups had a higher score than the treatment group with photodynamic therapy P2, P3 and P4 (p<0.05). This condition showed that in the P0 and P1 groups are still in the inflammatory phase, while in the P2, P3 and P4 groups have entered the remodeling phase which is characterized by high epithelialization scores and collagen density. Giving photodynamic therapy to wounds infected with MRSA can accelerate the wound healing process.